Pengukuran Beban Kerja Mental Menggunakan Metode NASA-TLX dan RSME Pada Divisi Engineering Desain CTVT & Dry Type PT. Trafoindo Prima Perkasa - Sri Lestari; Citra Mutiara; Zaenal Muttaqien (UNISTEK, 2026)
PT Trafoindo Prima Perkasa is an electrical transformer manufacturing company with an Engineering Design Division as a key part in supporting the production process, especially for CTVT and Dry Type transformers. However, in the period July?December 2024, a delay rate of 14% of the total 2,508 incoming orders was found in Engineering Job Orders (EJO). This study addresses the issue of high mental workload as one of the factors affecting the effectiveness of EJO implementation. The NASA-TLX and RSME methods were used to measure the mental workload of two engineers directly involved in the design process. The measurement results showed that the level of mental workload was in the high category, with NASA-TLX WWL scores of 82 and 88, and RSME scores of 128 and 120. Root cause analysis using a fishbone diagram and the 5W+1H method showed that the main causes of EJO delays included excessive workload, limited personnel, and deadline pressure. Proposed improvements include additional human resources, periodic workload evaluations, and adjustments to work policies. The results of both measurement methods were consistent, indicating a significant impact of mental workload on EJO delays. Keywords : Mental workload, Engineering Job Order, NASA-TLX, RSME, Fishbone diagram